2018
DOI: 10.1111/1541-4337.12324
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in the Microencapsulation of Functional Fatty Acid‐Rich Oils Using Transglutaminase Catalyzed Crosslinking

Abstract: Preparing stable protein-based microcapsules containing functional fatty acids and oils for food applications has been a big challenge. However, recent advances with transglutaminase (TGase) enzyme as an effective protein cross-linker could provide workable solutions for the encapsulation of omega-3 and omega-6 fatty acids without compromising their targeted release and their biological and physicochemical characteristics. The recent and available literature related to the microencapsulation techniques, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 103 publications
(244 reference statements)
0
29
0
Order By: Relevance
“…It has been reported that the amide I band is the most important secondary structure of proteins for FTIR analysis, while the shifting of amide peaks is characteristic for conformational change of random coil and α ‐helix type to more regular β ‐sheet structure of proteins . In addition, TGase is able to create covalent bonds between the γ ‐carboxyamide group of protein‐bound glutamine residues and the ε ‐amino group of protein‐bound lysine residues . All those interactions (shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the amide I band is the most important secondary structure of proteins for FTIR analysis, while the shifting of amide peaks is characteristic for conformational change of random coil and α ‐helix type to more regular β ‐sheet structure of proteins . In addition, TGase is able to create covalent bonds between the γ ‐carboxyamide group of protein‐bound glutamine residues and the ε ‐amino group of protein‐bound lysine residues . All those interactions (shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…All those interactions (shown in Fig. ) could enhance the intermolecular forces and the denseness of molecular chains among the main components of wall materials, providing excellent properties for protecting the core material, such as thickening and heat stability …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to an increase in denatured proteins caused by heating. Accordingly, the kinetic improvement of proteins was reorganized and MTG enzyme kept more whey proteins into the matrix (Gharibzahedi et al, 2018a). As a result, syneresis reduced and structure became more compact (Fig 1-2 and 3-4).…”
Section: Microstructures Of Ice Cream Samplesmentioning
confidence: 98%
“…This fact could be related to the kinetic improvement of protein reorganization induced by MTG enzyme at high temperatures. In heated milk, the MTG enzyme keeps more whey proteins into the matrix with reduced syneresis by changing the physical features of protein gels with low porosity (Gharibzahedi et al, 2018a). According to C ruz et al (2009), the melting time of ice cream is related to its stability after overrun.…”
Section: Physico-chemical Propertiesmentioning
confidence: 99%